Impies et païens : entre Antiquité et Moyen Age - Mary, Lionel; Sot, Michel (Paris Picard, 2002)
The evolution of the concept of impiety and paganism from the Classical period to early Christian times.
Keywords: Christianity and culture -- History -- Early church, ca. 30-600; Literature, Medieval -- History and criticism; Paganism -- Relations&delete& -- Christianity